The Caminhos dos Cânions do Sul UNESCO Global Geopark (Brazil) in scientific literature: A review - José Gustavo Santos da Silva; Ricardo Eustáquio Fonseca Filho; Juliano Bitencourt Campos; Mikael Miziescki; Nilzo Ivo Ladwig; Álvaro José Back; Emmaline M. Rosado-González; Artur Abreu Sá (International Journal of Geoheritage and Parks)
This research seeks to analyse scientific literature pertaining to Caminhos dos Cânions do Sul UNESCO Global Geopark (CCSUGGp) from 2007 to August 2024. The investigation involved searches utilizing the following keywords: “Geopark Caminhos dos Cânions do Sul,” “Geoparque Caminhos dos Cânions do Sul,” and “Southern Canyons Pathways.” The databases accessed for this purpose included Google Scholar, Scielo, Scopus, Web of Science, Digital Library of Theses and Dissertations, Spell, and Oasis/IBICT. A total of 198 works were documented, and through the application of the established inclusion and exclusion criteria, 29 scientific articles were identified and examined in both national (Brazilian) and international journals that conducted direct research within the CCSUGGp. A significant portion of the articles emphasized geosciences, while geotourism and education were addressed subsequently. An increase in scholarly works was observed following the international acknowledgment of the region. The municipalities within Santa Catarina State have become pivotal centres for research endeavours. Although this newly established model of territorial management in Brazil is relatively recent, the UNESCO Global Geopark demonstrates considerable potential for scientific inquiry.